The uncivil university intolerance on college campuses - Tobin, Gary A.; Weinberg, Aryeh Kaufmann; Ferer, Jenna (Lanham, Md. : Lexington Books, 2009)
Explores anti-Semitism and anti-Israelism and the rise of bigotry found on college campuses across America, and offers ways to combat it.
Something amiss in higher education -- Defining the civil university -- The emergence of the uncivil university -- The persistent prejudice -- Ideology and propaganda -- Uncivil politics and campus misconduct -- Reclaiming the civil university.
Includes bibliographical references (p. 285-289) and index.
Description based on print version record.
Keywords: Discrimination in higher education -- United States; Jewish students -- Crimes against -- United States; Antisemitism -- United States; EDUCATION / Higher; Electronic books